BIBLIOTECARII CA SPECIALIȘTI DE DATE - CONSTANTINESCU, informatician, București, Nicolaie (BIBLIOPOLIS, 2020)
The data context can no longer be ignored and can no longer be passed to an IT department. Librarians have to make a new revolution in terms of professional status. Quality data requires specialists to be „managed”, interpreted to comply with commonly accepted standards of interconnection and consumption. Librarians must acquire these skills. They have to understand that their profession is getting deeper and deeper with IT.